Development and Characterization of Fly Ash/Crumb Rubber Reinforced Natural Rubber Composite - Maan, Arti; Singh, Anil Kumar; Mehra, Dayal Singh; Rattan, Sunita (Asian Journal of Chemistry, 2015)
The aim of this study is to evaluate the feasibility of utilizing fly ash and crumb rubber derived from tyre waste with natural rubber to develop a composite material with improved properties. The composites were evaluated for morphological, thermal and mechanical properties. It was found that with increase in crumb rubber loading, tensile strength, tear strength, abrasion resistance and skid resistance of the composites increased whereas water absorption, compression set, hardness and density decreased up to 120 phr of crumb rubber concentration. SEM micrographs show that fly ash/crumb rubber reinforced natural rubber composites have enhanced rubber-filler interaction to produce more continuous and interlocked structure than fly ash reinforced natural rubber composite.